New-onset urethral stricture after transurethral holmium laser enucleation of the prostate and analysis on its influencing factors - WANG Jie; WANG Jie; YE Chenxi; YE Chenxi; HU Qiang; HU Qiang (陆军军医大学学报, 2025)
Objective‍　‍To systematic analyze the risk factors for new-onset urethral stricture after transurethral holmium laser enucleation of the prostate （HoLEP） in the treatment of benign prostatic hyperplasia （BPH）. ‍Methods‍　‍A case-control study was conducted on 746 BPH patients undergoing HoLEP treatment in Department of Urology of the Third Medical Center of Chinese PLA General Hospital from November 2021 to August 2024. After 23 cases were excluded because of complication of prostate cancer， finally 723 patients were included. General clinical data such as age， height， weight， history of smoking and drinking， perioperative parameters， and follow-up data at 1， 3 and 6 months after operation were collected. Univariate and multivariate logistic regression analyses were used to identify the clinical risk factors for new-onset urethral stricture after HoLEP. Results‍　‍The subjected patients had a median age of 66.5 （64.0， 75.0） years， and a preoperative median prostate volume of 66 （45， 92） mL， and a median indwelling catheter time of 4 （4， 5） d. The incidence of new urethral stricture after operation was 5.8% （42/723）， with membranous part of the urethra （61.9%） the most common site， followed by the external urethral orifice （21.4%） and the bladder neck （7.1%）. Risk factor analysis indicated that low BMI （<18.5 kg/m²） （OR=4.682， P=0.037）， young age （OR=0.946， P=0.005）， and postoperative urinary tract infection （OR=4.513， P=0.001） were independent risk factors for new-onset urethral stricture after surgery. Prostate volume and indwelling time of urinary catheter had no significant association with the occurrence of new urethral stricture after surgery. Conclusion‍　‍The occurrence of new-onset urethral stricture after HoLEP is significantly correlated with BMI， age and urinary tract infection. The above 3 factors can be used as better predictors of new-onset urethral stricture after HoLEP.